Pengaruh Analisis Break Even Point Dalam Meingkatkan Tingkat Pendapatan Industri Kecil (Study Kasus Usaha Batako Ahmad): The Effect of Break-Even Point Analysis on Increasing the Income Level of Small Industries (Batako Ahmad Business Case Study) - Ari Nurcahyo Darmawan; Budi Iriani Yudaningrum; Dita Rachmawati (JOURNAL KOPERASI DAN MANAJEMEN, 2022)
The aims of this research are: 1) to know the calling (unit and rupiah) that must be done by Batako Pitoyo business to be at a point BEP; 2) To know the amount of selling (units and rupiah) that must be done by Batako Pitoyo business to achieve profit, the planned amount is Rp 540.000.000; 3) To know the percentage of sales decrease (based on the budget) to be at a certain point BEP. The data collection instruments used in this research are: 1) Documentation, which is a collection of notes obtained from various written sources, whether they are from Batako Pitoyo or other businesses with a relationship to the research, documentation is a note taken in the past such as notes, books, and others. 2) Interviews are a method of collecting the data by question and answer or by communicating directly with people who have experience with the problems in the research to get better data. The results of the research show that: 1) the minimal sales volume that should be done by Batako Pitoyo to be at a point BEP amounted to 252.370 units, or Rp 656.162.532; 2) the volume of sales that must be done by Batako Pitoyo to achieve the planned profit during 2018 amount to Rp 540.000.000, or 966 362 units, or Rp 2.512.542.955; and 3) the percentage decrease in sales (on a budget) to be at a point BEP is 68%.